2020
DOI: 10.1111/wvn.12417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Outcomes of a Web‐Based Stress Management Program for Nurses and Nursing Assistants

Abstract: Objective The purpose of this quality improvement project was to determine the utilization, satisfaction, and effect of a web‐based stress management program for nurses and nursing assistants (NAs). Methods This quality improvement project provided BREATHE, a web‐based stress management program that consisted of six modules that describe, identify, and help nurses manage stress for 31 nurses and NAs working on a subacute rehabilitation unit at a mid‐Atlantic community hospital. Measurements The number of login… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…The American Organization of Nurse Executives (AONE, 2016) acknowledged the value of transformational leadership style in nurse managers as one that can foster higher rates of staff nurse achievements. The ongoing primary goal in health care is to provide high-quality, cost-efficient patient care (Dutton & Kozachik, 2020). This cannot be accomplished without the involvement of staff nurses and the support of their nurse managers (Institute of Medicine, 2010).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The American Organization of Nurse Executives (AONE, 2016) acknowledged the value of transformational leadership style in nurse managers as one that can foster higher rates of staff nurse achievements. The ongoing primary goal in health care is to provide high-quality, cost-efficient patient care (Dutton & Kozachik, 2020). This cannot be accomplished without the involvement of staff nurses and the support of their nurse managers (Institute of Medicine, 2010).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Other original studies identified four practical tools or methods, i.e., the Failure Mode and Effects Analysis (FMEA), 52 the Activities of Daily Living (ADL) scale, 59 the Quality Control Circle, 69 and an information sheet to patients, 73 as well as two valuable programmes on stress and CNA-patient relationships. 41 58…”
Section: Resultsmentioning
confidence: 99%
“…Emotional effects of burnout include mental exhaustion, depersonalization, perception of decreased personal and professional accomplishments, depression, and anxiety. 4,5 Physical effects include headaches, back and muscle pain, reduced energy, weakened immune systems, and changes in eating and sleeping routines. 4 These emotional and physical effects also can threaten patient safety.…”
mentioning
confidence: 99%
“…4,5 Physical effects include headaches, back and muscle pain, reduced energy, weakened immune systems, and changes in eating and sleeping routines. 4 These emotional and physical effects also can threaten patient safety. 1,4 "Burnout is a continuum on which everyone falls," Sieg said.…”
mentioning
confidence: 99%
See 1 more Smart Citation